A pilot study of dimethyl fumarate in pulmonary arterial hypertension associated with systemic sclerosis. Issue 3 (October 2021) - Kong, Kristi; Koontz, Diane; Morse, Christina; Roth, Eileen; Domsic, Robyn T; Simon, Marc A; Stratton, Eric; Buchholz, Connor; Tobin-Finch, Kimberly; Simms, Robert; George, M Patricia; Hassoun, Paul M; et al.
Introduction: Given the poor treatment options for pulmonary arterial hypertension–associated systemic sclerosis patients, we sought to determine clinical safety and efficacy of dimethyl fumarate, an Nrf2 agonist, and the effects on biomarkers of oxidative stress on pulmonary arterial hypertension–associated systemic sclerosis in an exploratory interventional clinical trial. Objectives: The primary objectives were to assess the safety and efficacy of treatment with dimethyl fumarate in patients with pulmonary arterial hypertension–associated systemic sclerosis. Methods: This was an investigator-initiated, double-blind, randomized, placebo-controlled trial conducted at two sites in the United States. The primary safety endpoint was the incidence of serious adverse events and all adverse events in dimethyl fumarate compared to placebo-treated patients. The primary efficacy endpoint was the change in 6-min walk distance from baseline to the end of treatment at Week 24 in dimethyl fumarate compared to placebo-treated patients. Results: Six participants were randomized to either placebo (n = 2) or dimethyl fumarate (n = 4). Baseline demographics were similar in both groups. A total of 25 adverse events occurred in 6 subjects, with 14 adverse events (56.0%) having occurred in dimethyl fumarate-treated subjects. Three occurrences were identified as nausea adverse events, and two participants withdrew due to nausea. One participant in the placebo group was withdrawn after a hospitalization serious adverse event due to worsening of heart failure and shortness of breath secondary to anemia. One participant in each group completed protocol. Subjects in the dimethyl fumarate-treated group showed a non-significant reduced decline in 6-min walk distance (relative mean change of −7.07%) from baseline to Week 24 as compared to placebo-treated subjects (relative mean change of −14.97%). Conclusion: Patients treated for pulmonary arterial hypertension–associated systemic sclerosis with 2- and 3-drug regimens, as is now typical for these patients, tolerate dimethyl fumarate poorly. Our small sample size did not provide power to suggest efficacy. We suggest that Nrf2 is still a valid therapeutic target for future trials, using better tolerated Nrf2 agonists.